Heterogeneity of expression of epithelial–mesenchymal transition markers in melanocytes and melanoma cell lines - Kim, Ji Eun; Leung, Euphemia Y.; Baguley, Bruce C.; Finlay, Graeme J. (Frontiers in Genetics, 2013)
The epithelial-mesenchymal transition (EMT) describes a reversible switch from an epithelial-like to a mesenchymal-like phenotype. It is essential for the development of the normal epithelium and also contributes to the invasive properties of carcinomas. At the molecular level, the EMT transition is characterised by a series of coordinated changes including downregulation of the junctional protein E-cadherin (CDH1), up-regulation of transcriptional repressors of E-cadherin such as Snail (SNAI1) and Slug (SNAI2), and up-regulation of N-cadherin. We wished to determine whether cultured normal melanocytes and melanoma cell lines, which are derived from the neural crest, showed signs of a similarly coordinated phenotypic switch. We investigated normal melanocytes and 25 cell lines derived from New Zealand patients with metastatic melanoma. Most lines had been previously genotyped for common mutations such as BRAF, NRAS, PIK3CA, TP53 and CDKN2A. Expression of E-cadherin, N-cadherin, MITF, Snail, Slug, Axl, p53 and Hdm2 was compared by western blotting. Normal melanocytes expressed each of these proteins except for Snail, while normal melanocytes and almost every melanoma line expressed Slug. Expression of individual markers among different melanoma lines varied from high to low or undetectable. Quantitation of western blots showed that expression of MITF-M, the melanocyte-specific isoform of MITF, was positively related to that of E-cadherin but inversely related to that of N-cadherin and Axl. There was also no apparent relationship between expression of any particular marker and the presence of BRAF, NRAS, PIK3CA, TP53 or CDKN2A mutations. The results suggest that melanomas do not show the classical epithelial and mesenchymal phenotypes but rather display either high E-cadherin/high MITF-M expression on one hand, or high N-cadherin/high Axl expression on the other. These may correspond to differentiated and invasive phenotypes in vivo.